Describe all or just a few? The influence of verbal descriptors on Likert-type variables on items’ and scales’ distribution - Calapez, T.; Ramos, M.; Botelho, M. C. (Sociologia On Line, 2016)
The aim of this study is to examine whether and how the use of verbal descriptors at all categories or just at the extremes of 5-point Likert-type items influences the results. Each participant was requested to mark his/her level of agreement with 18 items concerning beliefs on mathematics, using one of the following forms: with verbal descriptors at all categories or just at the extremes. Respondents were found to use more intensively the extreme categories when only these were verbally described. However, these differences were not significant when using summated scales, except in case of severe skewness.